Utilising Innovation to Improve Bogies and Wheelsets Design - Waters Craig (Global Railway, 2020)
Transforming Rail Freight in the Digital Era, Improving the Motivation and Skills of the Workforce, Project Update: The Fermernbelt Crossing.